2021
DOI: 10.48550/arxiv.2102.02550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Einstein-Podolsky-Rosen Steering in Two-sided Sequential Measurements with One Entangled Pair

Jie Zhu,
Meng-Jun Hu,
Guang-Can Guo
et al.

Abstract: Non-locality and quantum measurement are two fundamental topics in quantum theory and their interplay attracts intensive focuses since the discovery of Bell theorem. Recently, non-locality sharing among multiple observers with one entangled pair has been predicted and experimentally observed by generalized quantum measurement -weak measurement. However, only one-sided sequential case, i.e., one Alice and multiple Bobs is widely discussed and little is known about the two-sided case.Here, we theoretically and e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…It is found that an arbitrary number of pairs of sequential and independent observers can witness entanglement, acting locally on two-qubit entangled states. This result is potentially of importance, given that it has been conjectured that not more than a single pair of observers can detect CHSH Bell-nonlocal correlations in the same scenario [37][38][39]. Assuming that the conjecture in the literature is true, our finding demonstrates a clear distinction between "entanglement nonlocality" and "Bell nonlocality", with respect to sequential witnessing by pairs of observers.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…It is found that an arbitrary number of pairs of sequential and independent observers can witness entanglement, acting locally on two-qubit entangled states. This result is potentially of importance, given that it has been conjectured that not more than a single pair of observers can detect CHSH Bell-nonlocal correlations in the same scenario [37][38][39]. Assuming that the conjecture in the literature is true, our finding demonstrates a clear distinction between "entanglement nonlocality" and "Bell nonlocality", with respect to sequential witnessing by pairs of observers.…”
Section: Discussionsupporting
confidence: 58%
“…Recently, it was also observed that it is possible to witness and recycle entanglement an arbitrary number of times using a CHSH Bell-local entangled state [26]. For other theoretical works in the direction of recyclability of entangled and nonlocal correlations, see [27][28][29][30][31][32][33][34][35][36][37][38][39][40]. For experimental works, see [41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…when θ 1,0 = θ 1,1 = π 4 for Alice [48,49]. In particular, network nonlocal sharing can also be divided into two different types of nonlocality sharing, passive and active network nonlocal sharing, according to the different motivations of the former observers Alice 1 and Charlie 1 .…”
Section: Noise Resistance Of Network Nonlocal Sharingmentioning
confidence: 99%
“…Nonlocal sharing has attracted extensive attention [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], and lots of relevant results have been published ever since, such as active and passive nonlocal sharing [35], quantum steering sharing [47] and so on. However, almost all discussions are limited to the case of one-sided sequential measurements, that is, an entangled pair is distributed to one Alice and multiple [48,49]. Such discrepancy may give a hint to exhibit the different properties between network nonlocality and Bell nonlocality.…”
Section: Introductionmentioning
confidence: 99%